Ectopic insert-dependent neuronal expression of GFAP promoter-driven AAV constructs in adult mouse retina - Le, Nguyet; Appel, Haley; Pannullo, Nicole; Hoang, Thanh; Blackshaw, Seth (Frontiers in Cell and Developmental Biology, 2022)
Direct viral-mediated reprogramming of retinal Muller glia is a promising avenue for replacing photoreceptors and retinal ganglion cells lost to retinal dystrophies. However, questions have recently been raised about the accuracy of claims of efficient glia-to-neuron reprogramming in retina that were conducted using GFAP minipromoter-based adeno-associated virus (AAV) vectors. In this study, we have addressed this question using GFAP minipromoter-driven AAV constructs to simulaneously overexpress the mCherry reporter and candidate transcription factors predicted to induce glia-to-neuron conversion, in combination with prospective genetic labeling of retinal Muller glia using inducible Cre-dependent GFP reporters. We find that, while control GFAP-mCherry constructs express faithfully in Muller glia, that 5 out of 7 transcription factor overexpression constructs tested are predominantly expressed in amacrine and retinal ganglion cells, but that genetic cell lineage analysis shows no evidence for glia-to-neuron conversion. These findings demonstrate major insert-dependent effects on AAV-based GFAP minipromoter specificity that preclude its use in inferring cell lineage relationships in this context.